Application of Semi-Mechanical Cocoa Pod Splitter to Reduce Mold Risk and Bean Damage - Minarti, Asnia Nia; Ismail, Ismail; Annisa, Humairah (Universitas Lambung Mangkurat, 2025)
Cocoa is a leading plantation commodity with high economic value. Yet its quality and productivity are often constrained by post-harvest handling, particularly by manual pod splitting, which risks damaging beans and causing fungal contamination. This community service method is a participatory approach that combines the transfer of appropriate technology and continuous mentoring, encompassing activities such as socialization, training, field implementation, evaluation, and strengthening digital marketing capacity. This community service aims to improve efficiency, maintain hygiene, and produce export-quality beans. The program was implemented in collaboration with the Kabuttu Farmer Group in Gattareng Village through participatory approaches, including socialization, training, field application, and monitoring and evaluation. Beyond technical aspects, the program also provides digital marketing assistance to expand distribution networks. The expected outcomes of the community service include scientific and mass media publications, intellectual property registration, and digital documentation. The anticipated impacts are increased farmer income, reduced bean damage, and the development of local cadres to ensure sustainability. This initiative is expected to serve as a replicable post-harvest technology model, contributing to farmer welfare, rural economic empowerment, and the achievement of sustainable development goals.